Implementing Practice Guides to Improve Cancer Symptom Management in Homecare: A Comparative Case Study. Issue 3 (August 2019) - Stacey, Dawn; Ludwig, Claire; Truant, Tracy; Carley, Meg; Bennis, Cindy; Gifford, Wendy; Kuziemsky, Craig; Nichol, Kathryn; Lafreniere-Davis, Nicole; Owens, Glenda; Roscoe, Diane; Roberts, Pamela; et al.
Symptoms experienced by clients with cancer often occur at home and can become life-threatening, posing serious safety concerns. This study evaluated implementation of evidence-informed symptom practice guides to enhance quality of cancer symptom support by homecare nurses. A comparative case study was conducted using the Knowledge to Action Framework. Case were created for each of six agencies providing nursing care within a regional homecare authority. A team of researchers and knowledge users (e.g., managers, educators, family member): (1) assessed factors influencing practice guide use (survey, interviews) at six agencies, (2) adapted 15 practice guides for local use, (3) implemented with interventions to address barriers, and (4) monitored use. Analysis was within and across cases. Of six nursing agencies, one withdrew and five participated. In the baseline survey, 51% of nurses reported using guidelines but nurses did not describe using them in their current practice during the interviews. To overcome barriers, 489 nurses in five agencies were trained in how to use the practice guides, principles were established for documenting cancer symptom management, and practice guides were made available in various formats. Success with implementation varied across the participating cases. Chart audits conducted in three agencies revealed evidence of practice guide use for 16%, 22%, and 70% client visits, respectively. Implementation of evidence-informed practice guides in nursing required an approach tailored for each agency. Training, integration in documentation, and easy access to practice guides increased use for some nurses but ongoing support and reinforcement from nurse leaders is required.